ANALISIS KEIKUTSERTAAN INDONESIA DALAM INISIATIF SEKTORAL UNTUK PRODUK PERIKANAN, KIMIA DAN KEHUTANAN - Adrian D. Lubis (Buletin Ilmiah Litbang Perdagangan, 2008)
Sectoral initiative is an alternative to obtain better market access through the deletion of tariffs for some products or certain sectors. The negotiations sectoral initiatives consists of 12 sectors, but in this study only focuses on three main sectors, namely fisheries, chemical and forestry. The analysis performed in this study using three approaches: 1. Effective Rate Protection (ERP; 2. Constant Market Share Analysis (CMSA); and 3. General Equilibrium Models. The study found that the fisheries sector is the most ready to face the deletion of the tariffs because its relatively unprotect and competitive in the world. As for forestry products, tariff deletion in the sectoral initiative is expected will not provide benefits due to raw material shortages (moratorium) which reduces the competitiveness of Indonesia in the world. While chemical products today have high protection and less competitive, the deletion of the tariff is predicted will lead to an increase in imports. However, if the goal is to achieve cheaper raw materials in the chemical industry, this product is recommended to be include in sectoral initiatives.